How absent negativity relates to affect and motivation: an integrative relief model - Deutsch, Roland; Smith, Kevin J. M.; Kordts-Freudinger, Robert; Reichardt, Regina (Frontiers in Psychology, 2015)
The present paper concerns the motivational underpinnings and behavioral correlates of the prevention or stopping of negative stimulation – a situation referred to as relief. Relief is of great theoretical and applied interest. Theoretically, it is tied to theories linking affect, emotion and motivational systems (Carver & Scheier, 1990; Gray & McNaughton, 2000; Higgins, 1997; Lang, Bradley, & Cuthbert, 1990). Importantly, these theories make different predictions regarding the association between relief and motivational systems. Moreover, relief is a prototypical antecedent of counterfactual emotions, which involve specific cognitive processes compared to factual or mere anticipatory emotions. Practically, relief may be an important motivator of addictive and phobic behaviors (Mowrer, 1951; Ostafin & Brooks, 2011), self destructive behaviors (Favazza, 1998; Franklin, Lee, Hanna, & Prinstein, 2013), and social influence (Dolinski & Nawrat, 1998). In the present paper, we will first provide a review of conflicting conceptualizations of relief. We will then present an integrative relief model (IRMO) that aims at resolving existing theoretical conflicts. We then review evidence relevant to distinctive predictions regarding the moderating role of various procedural features of relief situations. We conclude that our integrated model results in a better understanding of existing evidence on the affective and motivational underpinnings of relief, but that further evidence is needed to come to a more comprehensive evaluation of the viability of IRMO.